Retinoblastoma gene product as a downstream target for a ceramide-dependent pathway of growth arrest. - Dbaibo, G S (1995)
Ceramide, a lipid mediator, has been most closely associated with antiproliferative activities. In this study, we examine the mechanism by which ceramide induces growth suppression and the role of the retinoblastoma gene product (Rb) in this process. Withdrawal of serum from the serum-dependent MOLT-4 cells resulted in significant dephosphorylation of Rb, correlating with the induction of G0/G1 cell cycle arrest. Serum withdrawal resulted in marked elevation in the levels of endogenous ceramide (3-fold at 24 h and 8-fold at 96 h) with little changes in the endogenous levels of sphingosine. The addition of exogenous C6-ceramide resulted in a concentration- and time-dependent dephosphorylation of Rb. Exogenous ceramide was active at levels comparable to endogenous levels achieved with serum withdrawal. Peak activity of exogenous ceramide (at 6 h) correlated with the uptake of C6-ceramide by MOLT-4 cells. Next, a number of studies were conducted to determine whether Rb plays a role in ceramide-induced growth suppression. (i) C6-Ceramide was poorly active in growth suppression of retinoblastoma cells that lack Rb. (ii) Mink lung epithelial cells in which Rb had been sequestered by overexpression of large tumor antigen were resistant to the action of ceramide compared to cells transfected with large tumor antigen mutated in the Rb-binding pocket. (iii) Overexpression of the EIA adenoviral protein, which binds and sequesters Rb, resulted in protection from growth suppression and cell cycle arrest induced by ceramide. Thus, these studies demonstrate that Rb is a downstream target for ceramide and may function in a growth suppressor pathway resulting in cell cycle arrest.